ANALYSIS OF THE STATUS OF THE GIRIAN WATERSHED IN BITUNG CITY DUE TO HOUSEHOLD WASTE POLLUTION - Rivaldo Tompoh; Arrijani Arrijani; Nova Ogi (Indonesian Biodiversity Journal, 2022)
The Girian watershed with a length of 17.5 km is the longest river in Bitung City which flows through a densely populated area as well as various industries such as smoked fish, tofu and tempeh, animal husbandry, agriculture, and industrial fish factories whose waste goes directly to the Girian watershed. The great deal of population activities can have an impact on water quality and the Girian watershed ecosystem. This study aims to analyse the water quality of the Girian watershed caused by domestic waste. This study uses a quantitative descriptive approach and the method used in this study is the Indonesian National Standard (SNI) according to the water quality parameters that have been determined. The results of the analysis of water quality upstream to downstream show that there is a decrease in water quality. Upstream is classified as good when compared to the parameters that have been determined. Densely populated areas begin to experience a decrease in water quality, namely with DO and Oil and Fat that exceeds the predetermined quality standard. As well as estuaries that have concentrations of TSS, NH3-N, Oils and Fats, COD, and BOD that exceed the specified quality standards. The results of the calculation of the pollution index show that station point 1 upstream is classified as good in 4 groups, station point 2 in densely populated areas shows lightly polluted results in group 2, and The Station 3 estuary shows moderate pollution results in group 3